HIF-1α Regulates Osteogenesis of Periosteum-Derived Stem Cells Under Hypoxia Conditions via Modulating POSTN Expression - Zhuang, Yu; Zhao, Zhiyang; Cheng, Mengjia; Li, Meng; Si, Jiawen; Lin, Kaili; Yu, Hongbo (Frontiers in Cell and Developmental Biology, 2022)
Periosteum is indispensable in bone repair and it is also an important skeletal stem cells (SSCs) source for endogenous bone regeneration. However, there are few studies about SSCs in periosteum. The cranio-maxillofacial bone regeneration is proceeded under hypoxia microenvironment, and HIF-1α plays an important role. The effect of HIF-1α on periosteum derived stem cells (PDSCs) and the mechanisms of PDSCs activation under hypoxia condition are unknown. In this study, calvarial bone defect was established, with periosteum removed or retained, the results showing that the bone regeneration was severely impaired in the periosteum removed group. Furthermore, pluripotent PDSCs isolated from periosteum were positive for mesenchymal stem cell (MSC) markers. To determine the role of HIF-1α, the expression of HIF-1α was knocked down in vivo and in vitro, and knockdown of HIF-1α expression impaired the bone regeneration or osteogenesis of PDSCs. Furthermore, the knockdown of HIF-1α expression also reduced periostin (POSTN) expression, and recombinant POSTN addition partly rescued the osteogenic inhibition. Finally, to explore the mechanism under POSTN activation, the phosphorylation level of PI3K/AKT pathway was assessed in transfected PDSCs. The phosphorylation level of PI3K and AKT was enhanced with HIF-1α overexpression and inhibited with HIF-1α knockdown, and the addition of PI3K activator or AKT activator could partly rescue POSTN expression. In conclusion, as potential target to promote bone repair under hypoxia microenvironment, HIF-1α can regulate the osteogenic differentiation of PDSCs via the PI3K/AKT/POSTN pathway, which lay a solid foundation for the periosteum-based cranio-maxillofacial bone regeneration.